KAJIAN TENTANG KEMAMPUAN SISWA DALAM MENGIDENTIFIKASI JENIS-JENIS IKATAN PADA SENYAWA KIMIA YANG TERDAPAT DALAM BUKU PAKET KIMIA SMA OLEH SISWA KELAS XI SMA NEGERI I GORONTALO ( Suatu Penelitian Di SMA Negeri 1 Gorontalo ) - Salilung, Pratiwi; Pikoli, Masrid; Sihaloho, Mangara (Jurnal Entropi, 2009)
This research is descriptive method, the aim of this research is to know the students ability to determine the kinds of chemical compound which found from SMA text book. The population in this research at class XI IPA SMA Negeri 1 Gorontalo concist of 93 students academic year 2008/2009. The sample of this research are students XIIB1, XIIB2, XIIB3 and XIIB4. To collecting the sample of research based on the average of the class according to the information which I get from the teacher. The instrument of this research by using the text and three alternative answer, and one of the answer 35 items. The result of experimental text get validasi is 85,66% and the reabilities koefisien is 0,92. The result of this research shows that the percentage of the students at class II SMA Negeri 1 Gorontalo who can be identify the kinds of chemical compound include in SMA text book, they are : (a) the bond ionic of ion kation and anion (28%), (b) the bond of kovalen nonpolar at chemical homodiatomic (86%), (c) the bond kovalen polar at the chemical heterodiatomic (50%), (d) the bond ionic at the yudium with simple kation and anion polyatomic (15%), (e) the bond of ionic at the yudiom with kation and anion polyatomic (46%), (f) the bond kovalen polar at the ion polyatomic in one yudium (54%), (g) the bond kovalen polar at the ion polyatomic (75%). The patterns of the students mistakes it can be identifier, there are: (a) relation between the same of two atom nonlogam is a relation with kovalen polar, (b) relations of the differences between two of nonlogam include of ionic compound, (c) relation between cation and anion in one of yudium include kovalen compound polar, (d) relation between cation and anion in one of yudium include kovalen compound polar, (e) relation in between kation and anion in one of yudiom include kovalen compound nonpolar, (f) relation between atom logam and atom nonlogsm include of kovalen compound nonpolar, (g) relation between atom logam and nonlogam of polar.